Odpowiedzi

2009-11-28T11:44:17+01:00
A) x+3y=3
x-y=5

x=3 - 3y
(3 - 3y) - y = 5

3 - 3y - y = 5
-3y - y = 5 - 3 |*(-1)
3y + y = -5+3
4y = -2 |:4
y = -½

x+3y=3
*x-y=5

x - (-½) = 5
x + ½ = 5
x = 5-½
x=4½


c) 3m+n=9
2m-5n=-11

n = 9 - 3m
2m - 5(9 - 3m) = - 11
2m - 45 + 15m = -11
17m = -11 +45
17m = 34 |:17
m=2

*3m+n=9
2m-5n=-11

3*2 +n = 9
n=9-6
n=3


e) 5x+4=2y
4x+y=3

Tu jest błąd, czegoś brakuje. prześlij mi ten przykład na prv to Ci go rozwiążę też.

b) 2x-y=10
x+5y=-17

-y = 10 - 2x |*(-1)
y = - 10 + 2x

x + 5(-10 +2x)=-17
x -50 + 10x = -17
11x=-17+50
11x=33 |:11
x=3

*2x-y=10
x+5y=-17

2*3 - y = 10
6 - y = 10
-y = 10 - 6
-y = 4 |*(-1)
y = -4

d) 4a-2=b
3a+7b=1,5

3a + 7(4a - 2) = 1,5
3a + 28a - 14 = 1,5
31a = 1,5 + 14
31a = 15,5 |:31
a = 2

*4a-2=b
3a+7b=1,5

4*2 - 2 =b
8 - 2 = b
b = 6


f) 6x-3y=9
x+5y=9,5

x = 9,5 - 5y
6(9,5 - 5y) = 9
57 - 30 y = 9
-30y = 9 - 57 |*(-1)
30y = 48 |:30
y = 1,6

6x-3y=9
*x+5y=9,5

x + 5*1,6 = 9,5
x = 9,5 - 8
x = 1,5

Pozdrawiam!
Najlepsza Odpowiedź!
2009-11-28T12:23:54+01:00
A){x+3y=5
x=y+5
{y+5+3y=5
x=y+5
{4y=5-5
x=y+5
{4y=0I:4
x=y+5
{y=0
x=y+5
{y=0
x=0+5
{y=0
x=5
b){2x-y=10
x=-5-17
{2(-5y-17)-y=10
x=-5y-17
{-10y-34-y=10
x=-5y-17
{-11y=34+10
x=-5y-17
{-11y=44I:(-11)
X=-5y-17
{y=4
x=-5y-17
{y=4
x=-5*4-17
{y=4
x=-20-17
{y=4
x=-37
c){n=-3m+9
2m-5*(-3m+9)=-11
{n=-3m+9
2m+15m-45=-11
{n=-3m=9
17m=45-11
{n=-3m+9
17m=34I:17
{n=-3m+9
m=2
{n=-3*2+9
m=2
{n=-6+9
m=2
{n=3
m=2
d){-b=-4a+2I*(-1)
3a+7b=1,5
{b=4a-2
3a=7b=1,5
{b=4a-2
3a=7(4a-2)=1,5
{b=4a-2
3a+28a-14=1,5
{b=4a-2
31a=14+1,5
{b=4a-2
31a+15,5I:31
{b=4a-2
a=½
{b=4*½-2
a=½
{b=2-2
a=½
{b=0
a=½
e){5x+4-2y=0
y=-4x+3
{5x+4-2(-4x+3)=0
y=-4+3
{5x+4+8x-6=0
y=-4x+3
{13x=-4+6
y=-4x+3
{13x=2I:13
Y=-4X+3
{x=²/₁₃
{ y=-4*²/₁₃+3
x=²/₁₃
{y=⁸/₁₃+3
x=²/₁₃
{y=3⁸/₁₃
x=²/₁₃